Impact of COVID-19 and Consortium Factors on Mental Health: Role of Emotional Labor Strategies in Achieving Sustainable Development Goals - Rehman, Saqib; Hamza, Muhammad Ali; Nasir, Adeel; Ullah, Aman; Arshad, Nabeela (Frontiers in Psychology, 2022)
The COVID-19 pandemic that began in 2019 has created an acute fear of economic crisis, and people have experienced the state of perceived job insecurity. Several measures were taken to control this deadly pandemic, but it still affected the majority of global operational activities. This study addresses the United Nation’s Sustainable Development Goal (SDG) number 8 that relates to decent work and economic growth. This quantitative study examines the impact of fear associated with economic crisis and perceived job insecurity on mental health with the moderating effect of surface and deep acting. Surface acting is displaying fake emotions, and deep acting is modifying inner feelings according to the required emotions. This study used sample data from private-sector employees and applied SmartPLS for structural model assessment. As many organizations took more challenging decisions to sustain their business operations, the study therefore analyzes the impact of the pandemic on private sector employees. The two main findings of the study are: (i) surface acting moderates the relationships of fear of economic crisis and perceived job insecurity with mental health and declines the impact of both on mental health, (ii) while deep acting negatively moderates the relationships of fear of economic crisis and perceived job insecurity with mental health and improved mental health even in the presence of both. The study highlighted the importance of deep acting at workplaces to sustain employees’ mental and psychological stability. Organizations could introduce emotional labor strategies and strengthen the mental health of their employees against the underlying fear of economic crisis and perceived job insecurity.